Thermal performance of different integration schemes for a solar tower aided coal-fired power system - Li, Chao; Zhai, Rongrong; Yang, Yongping; Patchigolla, Kumar; Oakey, John E. (Elsevier, 2018)
A Solar Tower Aided Coal-fired Power (STACP) system utilizes a solar tower coupled to a conventional coal-fired power system to reduce pollutants, greenhouse gas emissions and the investment of solar energy facilities. This paper examines three different schemes for integrating solar energy into a conventional boiler. For each scheme, an energy and exergy analysis of a 600 MWe supercritical coal-fired power system is combined with 53 MWth of solar energy in both a fuel saving mode and a power boosting mode. The results show that, for all these integration schemes, the boiler’s efficiency and system’s efficiency are reduced. However, the standard coal consumption rate is lower in comparison to conventional power plants and the standard coal consumption rate in the fuel saving mode is lower than that in the power boosting mode for all three schemes. Comprehensively considering both the standard coal consumption rate and efficiency, the scheme that uses solar energy to heat superheat steam and subcooled feed-water is the best integration option. Compared with a coal-fired only system, the saved standard coal consumption rate of the above mentioned scheme in fuel saving mode and power boosting mode can reach up to 11.15 g/kWh and 11.11 g/kWh, respectively. Exergy analysis shows, for STACP system, exergy losses of boiler and solar field contribute over 88% of whole system’s exergy loss.
Keywords: Solar tower power system; Coal-fired power system; Fuel saving mode; Power boosting mode; Exergy analysis